2022
DOI: 10.1038/s41467-022-32815-x
|View full text |Cite
|
Sign up to set email alerts
|

Marine phosphate availability and the chemical origins of life on Earth

Abstract: Prebiotic systems chemistry suggests that high phosphate concentrations were necessary to synthesise molecular building blocks and sustain primitive cellular systems. However, current understanding of mineral solubility predicts negligible phosphate concentrations for most natural waters, yet the role of Fe2+, ubiquitous on early Earth, is poorly quantified. Here we determine the solubility of Fe(II)-phosphate in synthetic seawater as a function of pH and ionic strength, integrate these observations into a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…Geochemical models suggest high concentrations of P i (>1 M) would accumulate coincidently with high concentrations of carbonate in natural (prebiotic) environments. 21 Interestingly, we observe carbonate has no detrimental effect on the observed Pro /P i catalysed aldol (ESI,† Fig. S39 and S40).…”
mentioning
confidence: 73%
“…Geochemical models suggest high concentrations of P i (>1 M) would accumulate coincidently with high concentrations of carbonate in natural (prebiotic) environments. 21 Interestingly, we observe carbonate has no detrimental effect on the observed Pro /P i catalysed aldol (ESI,† Fig. S39 and S40).…”
mentioning
confidence: 73%
“…A final consideration affecting the estimates of total seawater P concentrations relates to the presence of dissolved Fe(II), which is demonstrated by the occurrence of greenalite and siderite in the jaspilites. Brady et al ( 64 ), on the basis of new and existing solubility data for the Fe-phosphate system in seawater, showed that dissolved Fe(II) leads to strong aqueous complexing with dissolved phosphate species, in turn, increasing the solubility of all phosphate minerals. Accounting for this effect leads to even higher estimates for seawater P concentrations, which, for 10-nm FAP particles, corresponds to 10 to 60 μmol/kg (at pH 7) to 40 to 150 μmol/kg (at pH 6.5) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Third, phosphate is geochemically more widely available than simple organic thiols. 61–64 Furthermore, whereas acyl phosphates do not contain sulfur, thiol-based leaving groups in metabolism, such as CoA, generally contain phosphoryl groups. Fourth, in water, the formation of acyl phosphates from carboxylates is arguably chemically simpler than the conversion of carboxylates to thioesters – the former requires only a single component (an activated phosphate), whereas the latter requires two (a thiol and an activating agent for the carboxylate).…”
Section: Discussionmentioning
confidence: 99%